Review: Sunnyside. A Sociolinguistic History of British House Names. By Laura Wright. Cambridge University Press, 2020. Pp. xviii, 281 - Rutkowska, Hanna (Studia Anglica Posnaniensia, 2023)
Review: Sunnyside. A Sociolinguistic History of British House Names. By Laura Wright. Cambridge University Press, 2020. Pp. xviii, 281.